Assurance of Learning (AOL) Case Study in a Capstone Finance Course at Indiana University South Bend - KOhli, Raj K (Archives of Business Research, 2018)
Assurance of Learning (AOL) has become an increasingly important dimension in Association to Advance Collegiate Schools of Business (AACSB) evaluation standards. In this case study, the author has developed and used a distinct AOL model to measure the impact on students learning in a capstone finance course at a state university in Indiana. Direct assessment of students learning is tested in closely controlled classroom environment through exam. The findings of the AOL model application indicate average scores of 81.61 percent for the semester, 85.67 percent for uncontrolled non-AOL model application environment, and 58.60 percent for controlled AOL model application condition respectively. Eighteen of twenty students in the study performed poorly in the AOL model application category than non-AOL model category. A poor performance in AOL model category indicates that the AOL model developed for this study successfully measures Assessment Process.